Upaya Peningkatan Kemampuan Berbicara Anak Usia 4-5 Tahun Melalui Metode Bercakap-Cakap Di TK Darussalam Pipitan - Mastariyah Mastariyah; Yahdinil Firda Nadhirah; Khaeroni Khaeroni (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2019)
This study was classroom action research study which conducted at TK Darussalam Piptan to improve conversation ability at 4 to 5 years old early childhood children by employing conversation method. This study used two cycles and the result of study shows that there was a significant improvement at 4 to 5 years old early childhood children at TK Darussalam Pipitan. Based on the result of study the completeness attainment on cycle I was 30% and did not reach treatment success indicator. Keywords: Children's speaking ability, conversation methode, effortReferencesBrown, D. (2007). Prinsip Pembelajaran Dan Pengajaran Bahasa. Jakarta: Pearson Education,Inc.Ciptarja, B. (2008). How To Teach Your Baby Talk. Yogyakarta: Andi Offset.Djiwandono, M. S. (1996). Bahasa Dalam Pengajaran. Jakarta: Index.Fitriyyah, D. (2016). Membangun Karakter Anak Melalui Dongeng. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 1–10.Humaeroh, H. (2016). Pembelajaran Bahasa Pada Anak Yang Mengalami Keterlambatan Berbicara Untuk Meningkatkan Kemampuan Berkomunikasi. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 126–138.Hurlock, E. B. (1980). Psikologi Perkembangan. Jakarta: Penerbit Erlangga.Imroatun, I. (2018). Alternatif Media Pengembangan Literasi Baca Tulis Berbahasa Nasional Bagi Siswa Raudlatul Athfal. Al Hikmah Proceedings on Islamic Early Childhood Education, 103–112. tuban: Program Studi PIAUD STAI Al Hikmah Tuban.Ma’isyah, N. (2018). Pengembangan Modul Membaca Lancar Pokok Bahasan Lingkungan Yang Bernuansa Kontekstual. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 137–146.McNiff, J., & Whitehead, J. (2002). Action research: principles and practice 2nd Edition. USA: Routledge Falmer.Moeslichatoen R. (2004). Metode Pengajaran Di Taman Kanak-Kanak. Jakarta: Rineka Cipta.Mursid. (2015). Belajar dan Pembelajaran PAUD. Bandung: PT Remaja Rosdakarya.Suhartono. (2005). Pengembangan Keterampilan Bicara Anak Usia Dini. Jakarta: Departemen Pendidikan Nasional.